Interviewee Transcript Review as a Tool to Improve Data Quality and Participant Confidence in Sensitive Research - James Rowlands (International Journal of Qualitative Methods, 2021)
Interviewee Transcript Review (ITR), a form of Respondent Validation, is a way to share and check interview transcripts with research participants. To date, the literature has considered how these practices affect data quality, focused on the ability of a participant to correct, add or remove data. Less considered is the extent to which ITR might enable sensitive research. Reporting on research examining the experiences and perspectives of different stakeholders involved in Domestic Homicide Reviews, 40 participants who took part in semi-structured interviews were offered the opportunity to review their transcripts. This paper contributes to the understanding of the use of ITR, demonstrating how it can be used to increase participant confidence to provide assurance about, and indeed active involvement in, the steps being taken to preserve their anonymity.